Moroccan public reforms inspired by New Public Management - EL MOUISSIA, Imane; BENABDELHADI, Abdelhay (Revue Internationale des Sciences de Gestion, 2021)
New Public Management is a management style that has taken the world by storm, redefining how the public sector operates everywhere. According to the precepts of the New Public Management movement, the public sphere should restructure its entire framework to include practices directly inspired by those used in the private sector such as governance, strategic planning, management of human resources, management control, auditing, since they’ve brought considerable results there. The Kingdom of Morocco has been influenced to modernize its public sector by many factors such as the state of its economic indicators, the will of the king and the relationship of the country with different international organizations, and the deep dissatisfaction of the tax paying citizens by the quality of the public service. To achieve that, over the last 20 years Morocco has introduced a plethora of changes aimed at reforming its public sector, many of these changes were directly inspired by the some of practices of the New Public Management. This paper aims therefor to review how these reforms were implemented.